This is my answer for this question (- 201) x= -1. X=4
Answer: 2.37
Step-by-step explanation:
Answer:
Number 4 is correct.
Step-by-step explanation:
rearrange the equation to where you set it equal to 0 by moving the 25 over.
n2 - 8n -9 = 0
now factor
(n-9)(n+1)
so n1 = 9
n2 = -1
Answer:
(B) The inequality that represents this relationship is ![3x < x^2 +15](https://tex.z-dn.net/?f=3x%20%20%3C%20x%5E2%20%2B15)
Step-by-step explanation:
Let us assume the given number = x
⇒ 3 times the given number = 3 (x) = 3x
Square of the given number = ![(x)^2 = x^2](https://tex.z-dn.net/?f=%28x%29%5E2%20%20%3D%20x%5E2)
Now, According to the question:
The difference of (3 x) and 15 is no less than ![x^2](https://tex.z-dn.net/?f=%20x%5E2)
⇒ ![3x - 15 < x^2\\ \implies 3x < x^2 +15](https://tex.z-dn.net/?f=3x%20-%2015%20%3C%20x%5E2%5C%5C%20%5Cimplies%203x%20%20%3C%20x%5E2%20%2B15)
or, ![3x < x^2 +15](https://tex.z-dn.net/?f=3x%20%20%3C%20x%5E2%20%2B15)
Hence, the given inequality is represented as ![3x < x^2 +15](https://tex.z-dn.net/?f=3x%20%20%3C%20x%5E2%20%2B15)